Integrated disease management of phyllody of sesame (Sesamum indicum L.): INTEGRATED DISEASE MANAGEMENT OF PHYLLODY OF SESAME - DATA RAM KUMHAR,; A K MEENA, (Journal of Oilseeds Research, 2016)
Sesame phyllody is an important disease caused by a pleomorphic phytoplasma which is transmitted by a leafhopper, Orosius albinctus. The affected plants become stunted and floral parts are modified in to leafy structures bearing no fruits and seeds causing yield loss up to 59.6 per cent. In this view, a field experiment was conducted at Agriculture Research Sub-Station, Hanumangarh, Rajasthan for the effective management of sesame phyllody through the application of antibiotics, botanicals and insecticides. The experiment was carried out to study the efficacyofseed treatment with imidacloprid and foliar spray ofinsecticides + combination ofstreptocycline + copper oxychloride. The treatment comprising seed treatment with imidacloprid 70WS @ 5g/kg seed followed by two sprays of thiomethoxam25WG @ 0.25 g/l at 40 and 50 DAS and one spray ofstreptocycline 150 ppm+ copper oxychloride 50WP @ 2g/l at 60 DAS gave minimum disease incidence of 2.5%, highest seed yield of 918 kg/ha as well as maximum cost benefit ratio of 1: 3.32 followed by seed treatment with imidacloprid 70WS @ 5g/kg seed + two sprays of thiacloprid 21.7SC @1ml/l + one spray of streptocycline 150 ppm + copper oxychloride 50WP @ 2g/l which was significantly superior over standard check with a per cent disease incidence of 11.7% and seed yield of 547 kg/ha.